Application of the Discovery Learning Model to Improve Mathematical Activities and Conceptual Understanding - Faturrachim, Hanif; Mahmudah Titi Muanifah; Sabarudin (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2025)
The learning process in higher education, particularly in education study programs, is not only oriented towards knowledge transfer, but rather emphasizes the development of prospective teachers' pedagogical capacity in designing and delivering contextual learning materials. The main challenge that often arises, especially among first-semester students, is the low level of active engagement in the learning process due to the still dominant one-way learning approach. Through mixed methods research (qualitative-quantitative) that combines observation, interviews, document analysis, and comprehension tests, it was found that the implementation of Discovery Learning succeeded in significantly increasing both student engagement and their conceptual understanding. Quantitative data showed an average post-test score of 93.13, while qualitative findings revealed the development of students' creative pedagogical abilities in designing innovative learning strategies such as educational songs, puzzle games for Roman numerals, and origami media for fractions. These results prove that the student-centered approach through Discovery Learning not only addresses engagement issues but also builds a more meaningful and applicable understanding of mathematics for prospective teachers and elementary school students.